2011
DOI: 10.1021/jp209466k
|View full text |Cite
|
Sign up to set email alerts
|

LSPR Imaging of Silver Triangular Nanoprisms: Correlating Scattering with Structure Using Electrodynamics for Plasmon Lifetime Analysis

Abstract: Here, an investigation into the optical response of truncated and nontruncated Ag triangular nanoprisms is presented. Single particle darkfield microspectroscopy and transmission electron microscopy (TEM) are performed to obtain an overview of the relationship between plasmonic properties and nanoparticle structure. A general framework is built to describe the optical response (resonant wavelength λmax and full width at half maximum (fwhm)) of triangle nanoprisms in a size regime (60–140 nm edge length) that h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
112
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(126 citation statements)
references
References 91 publications
7
112
2
1
Order By: Relevance
“…However, SPR lifetime can be influenced by radiative damping and surface scattering, and in most nano-particles studies, the SPR resonances spectrally overlap with interband transitions. [21,22,25,74] It is worth noting, however, that our measured τ = 17 ± 3 fs is consistent with the longest value of τ = 13 fs based on plasmonic resonance linewidth of a silver nano-particle at room temperature. [21,22,25] Interband effects…”
Section: Comparison Of Drude Parameters With Literature Valuessupporting
confidence: 88%
See 2 more Smart Citations
“…However, SPR lifetime can be influenced by radiative damping and surface scattering, and in most nano-particles studies, the SPR resonances spectrally overlap with interband transitions. [21,22,25,74] It is worth noting, however, that our measured τ = 17 ± 3 fs is consistent with the longest value of τ = 13 fs based on plasmonic resonance linewidth of a silver nano-particle at room temperature. [21,22,25] Interband effects…”
Section: Comparison Of Drude Parameters With Literature Valuessupporting
confidence: 88%
“…In addition, discrepancies between theoretical and experimental values of different optical and plasmonic properties of silver have raised concerns over the accuracy of some of the most widely used measurements of the dielectric function of silver. [18][19][20][21][22][23][24][25] Accurate values for the dielectric function of silver are needed in the visible and infrared (IR) spectral ranges, because many important parameters, such as surface plasmon propagation length, plasmon lifetime, non-radiative loss, and even the Casimir force, are sensitively linked to small variations of the dielectric function. [16] In this work, we provide a comprehensive measurement of the optical dielectric function (ω) of evaporated and template-stripped polycrystalline silver using spectroscopic ellipsometry, covering a broad spectral range throughout the mid-IR to Vis/UV of two orders of magnitude, from 0.05 eV to 4.14 eV (25 µm to 300 nm).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surface-assisted plasmon decay (Landau damping) has been extensively studied experimentally [33][34][35][36][37][38][39][40][41][42][43] and theoretically [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] since the pioneering paper by Kawabata and Kubo [44], who have shown that, for a spherical particle of radius a, the surface scattering rate is γ sp = 3v F /4a, where v F is the electron Fermi velocity. In subsequent quantum-mechanical studies carried within random phase approximation (RPA) [45][46][47][48][49][50][51] and timedependent local density approximation (TDLDA) [52][53][54][55][56][57][58][59] approaches, a more complicated picture has emerged involving the role of confining potential and nonlocal effects.…”
Section: Introductionmentioning
confidence: 99%
“…It was also demonstrated that energy-filtered transmission electron microscopy (EFTEM) can be equivalently employed to obtain the same information [8]. Plasmons in nanoparticles of other geometries were also visualized with SI methods [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. In particular, to investigate SERS activity, Guiton et al employed STEM-EELS to probe the fields of plasmons in silver nanorods and correlated this with far-field scattering spectroscopy [15].…”
Section: Introductionmentioning
confidence: 99%